Influence of dexamethasone and epinephrine on glycogen content and cytosol glucocorticoid receptors in hyperthyroid rat liver - Mi Zeng-Hui; Tian Ying; Cong Zheng (Acta Pharmacologica Sinica, 2016)
The influence of hyperthyroidism on the action of drugs affecting rat liver glycogen content and its mechanism were investigated. The thyroid-induced hyperthyroidism of rat served as the model. In normal rats, dexamethasone (5 mg.kg-1, ip) increased the content of liver glycogen and decreased the Bmax of glucocorticoid receptors (GCR) in liver cytosol. These effects were minimized or even disappeared in hyperthyroid rat models. On the other hand, in normal rats, epinephrine (0.20 mg.kg-1, ip) decreased the content of liver glycogen. This effect was potentiated in hyperthyroid rat models. Epinephrine did not affect the Bmax of GCR in liver cytosol of normal and hyperthyroid rats. These results suggested that hyperthyroidism may be one of the causes effecting the individual differences of drug action, and that the influence of hyperthyroidism on the glycogen-increasing action of dexamethasone correlated well with the changes in glucocorticoid receptor. The mechanism of the influence of hyperthyroidism on the glycogen-decreasing action of epinephrine is to be further explored.